(untitled) (REMUNOM, 2025)
Access and persistence in higher education represent significant challenges for rural Black youth in Brazil, impacted by historical, structural, and social barriers. This article’s objective is to expose the challenges faced by Black, low-income students from rural areas in their journey to higher education, highlighting the limits generated by historical and structural factors. The guiding research question is: what are the main historical, structural, and social challenges that rural Black youth face in accessing and persisting in higher education in Brazil?. The central argument is that the obstacles faced by this population are not isolated facts but the result of consolidated structural racism, intensified by the neglect of public policies aimed at the specificities of the countryside. The methodology is based on a qualitative approach, using a bibliographic review. The results indicate that educational exclusion is based on racial inequalities manifested in the absence of adequate structures, such as transportation, school infrastructure, and a contextualized curriculum. The literature review revealed that mobility difficulties, long distances, precarious transportation, and degraded school infrastructure are recurrent barriers. It is concluded that, despite advances in affirmative action policies, the majority of rural Black youth remain in unfavorable conditions, making it necessary to create and implement policies that address their specific demands to democratize access to higher education.